ANALISIS IMPLEMENTASI ETIKA PEMASARAN SYARIAH PADA BANK BSI KCP LUBUK SIKAPING - Widiati Lubis; Zulhelmi (CV. Adiba Aisha Amira, 2025)
In a town like Lubuk Sikaping, where sharia-observant Muslims make up the vast majority of the population, this study assumes that Bank BSI KCP Lubuk Sikaping can help the company grow and succeed. Employees at Bank BSI KCP Lubuk Sikaping have done an excellent job implementing sharia marketing ethics, which has helped the bank attract trustworthy clients who are interested in applying for loans. There has been a failure to execute measures pertaining to honouring promises and communicating with clients since some personnel have not fulfilled their commitments and others have made blunders in their communication. This study aims to examine the implementation of sharia marketing ethics at Bank BSI KCP Lubuk Sikaping and poses the problem of how marketing ethics are being implemented there. The researcher relied on Mikro Relation and a number of Bank BSI KCP Lubuk Sikaping customers as key informants in this qualitative study that aimed to observe all relevant situations and events in relation to the accurate abstraction. Researchers documented their findings and gathered information through interviews and participant observation. Research findings indicate that Bank BSI KCP Lubuk Sikaping has implemented sharia marketing ethics by conducting marketing activities in line with religious values, morals, sharia principles, and company regulations, as well as by following the principles and indicators of sharia marketing ethics.